Biomechanical model for simulating impacts against protective padding of sport facility - Valentini, P. P.; Pennestri, E.; Quattrociocchi, L. (Sports Engineering, 2016)
The paper deals with the development of an original numerical model able to simulate the dynamics of a human body impacting against sport protective structures at a low velocity. The model has been developed using the multibody dynamics approach and includes major bony parts, intervertebral discs, muscles and ligaments. Body interaction with the protective structures has been simulated with a three-dimension contact and using nonlinear stiffness elements evaluated by means of finite element investigations. The use of multibody model has been preferred due to the consideration that it combines the detailed description of the three-dimensional biomechanical systems with a smaller set of parameters to be defined with respect to finite element approach. The model has been used for assessing and comparing the protective performance of different padding shapes and materials in terms of head injury criteria.